Analysis of co-contraction of the trunk muscles in the side bridge stabilization exercise with different unstable surfaces (Bioscience Journal, 2019)
The muscle co-contraction is a phenomenon characterized by the simultaneous contraction of two or more muscles around a joint. The objective of this study was to compare the antagonist co-contraction of the local and global trunk muscles during side bridge exercise, in four situations: (a) stable; (b) instability in the upper limbs with bosu; (c) instability in the upper limbs with disc and (d) double instability. The sample consisted of 20 male volunteers and data collection was performed with simple differential surface electrodes. The electromyographic activity was collected from the Rectus Abdominis (RA), Internal Oblique Abdominis (IO), Multifidus (MF) and Erector Spinae (ES). Were utilized specific routines developed in the Matlab program (Mathworks Natick, USA) to calculate the percentage of antagonist co-contraction between local (IO/MF) and global muscles (RA/ES). The collected data were submitted to parametric statistical analysis (repeated measures ANOVA) or non-parametric (Friedman). The results demonstrated that no significant differences were observed in the pattern of global and local co-contraction in the different side bridge exercises with and without unstable surface. It is concluded that the use of unstable surface in the side bridge stabilization exercise does not increase the level of co-contraction of the trunk flexor and extensor muscles compared to normal stability. However, future studies should use a longer time of isometric contraction in trunk stabilization exercises to optimize the understanding of the effects of different unstable equipment on global and local levels of co-contraction of the trunk muscles.